Kierunki Rozwoju Termosprężystości - Nowacki, W. (Engineering Transactions, 1962)
This survey presents the results of investigations and the development trends that can be observed in some domains of thermoelasticity. The problem of coupling between the temperature field and the strain field is discussed as well as the problem of thermal stresses in anisotropic homogeneous bodies, isotropic non-homogeneous bodies and physically non-linear bodies.